2011
DOI: 10.1007/s00338-011-0839-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying coral abundance near low-pH springs: implications for future ocean acidification

Abstract: Rising atmospheric CO 2 and its equilibration with surface ocean seawater is lowering both the pH and carbonate saturation state (X) of the oceans. Numerous calcifying organisms, including reef-building corals, may be severely impacted by declining aragonite and calcite saturation, but the fate of coral reef ecosystems in response to ocean acidification remains largely unexplored. Naturally low saturation (X * 0.5) low pH (6.70-7.30) groundwater has been discharging for millennia at localized submarine springs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 24 publications
3
132
0
1
Order By: Relevance
“…Extension rates of P. cylindrica nubbins used in both the treatment and control flumes were similar to P. cylindrica from elsewhere in the GBR (31); however, this is not entirely surprising given that coral can maintain similar rates of extension under low-pH conditions at the cost of reduced skeletal density and hence rates of calcification (32). Nonetheless, we find that the skeletal densities in the low pH FOCE corals differed by less than 3% from the densities of control corals (Table S3).…”
Section: Resultssupporting
confidence: 53%
“…Extension rates of P. cylindrica nubbins used in both the treatment and control flumes were similar to P. cylindrica from elsewhere in the GBR (31); however, this is not entirely surprising given that coral can maintain similar rates of extension under low-pH conditions at the cost of reduced skeletal density and hence rates of calcification (32). Nonetheless, we find that the skeletal densities in the low pH FOCE corals differed by less than 3% from the densities of control corals (Table S3).…”
Section: Resultssupporting
confidence: 53%
“…study low Ω arag coincided with high nutrient levels (Crook et al, 2012), which could also cause increased bioerosion (Glynn, 1997). On the other hand Tribollet et al (2009) showed that coral blocks euendolithic micro-algae developed significantly under conditions of comparably low Ω arag levels at low nutrient levels (NH 4 + =0.4 µmole/L and PO 4 -3 =0.1 µmole/L).…”
Section: Discussionmentioning
confidence: 97%
“…Seepage of groundwater can lead to areas of high pCO 2 and low pH in coastal ecosystems (Basterretxea et al 2010). Groundwater with a low carbonate saturation state (Ω≈0.5) and reduced pH (6.70-7.30) seeps through the seafloor, creating localized low seawater pH in the natural submarine groundwater springs at Puerto Morales, Mexico (Crook et al 2012). Submarine volcanic vents or groundwater seeps can also lead to high CO 2 and low pH in surface coastal waters.…”
Section: Regulation Of Seawater Ph In the Pre-disturbed Holocene Oceanmentioning
confidence: 99%